2019
DOI: 10.1149/2.0152001jes
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Electrocatalytic Oxidation of Formic Acid at Platinum

Abstract: The formic acid oxidation reaction (FAOR) is a model electrocatalytic reaction involving multiple proton-coupled electron transfer steps. Despite of repeated research extending over more than fifty years, the FAOR is still an active research field in which several important questions including reaction mechanisms, the activity dependence on the electrode structure, the hysteresis between positive-and negative-going scan in cyclic voltammetry (CV), and, especially, the pH effect, remain elusive yet. To shed som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 51 publications
(118 reference statements)
1
30
0
3
Order By: Relevance
“…In general, when there is a net dipole change upon displacing the solvent with an adsorbate, there is a possibility for a second PZC, and therefore, this phenomenon is most likely not unique to the combination of platinum and OH intermediates (Frumkin and Petrii, 1975;Martnez-Hincapié et al, 2018). In addition to the ORR (Huang et al, 2016a;Zhang et al, 2019;Zhou et al, 2020), the double layer model above has been used successfully to model the formic acid oxidation (Zhu and Huang, 2019), and peroxodisulfate reduction (PDSR) reactions (Zhang and Huang, 2020) at Pt(111).…”
Section: Influence Of Surface Chargementioning
confidence: 99%
“…In general, when there is a net dipole change upon displacing the solvent with an adsorbate, there is a possibility for a second PZC, and therefore, this phenomenon is most likely not unique to the combination of platinum and OH intermediates (Frumkin and Petrii, 1975;Martnez-Hincapié et al, 2018). In addition to the ORR (Huang et al, 2016a;Zhang et al, 2019;Zhou et al, 2020), the double layer model above has been used successfully to model the formic acid oxidation (Zhu and Huang, 2019), and peroxodisulfate reduction (PDSR) reactions (Zhang and Huang, 2020) at Pt(111).…”
Section: Influence Of Surface Chargementioning
confidence: 99%
“…* 57. Consistently, with DFT computation, Huang's group found that HCOO m * is the main active intermediate with HCOO − as the main precursor, and HCOO b * is the site-blocking specie with HCOOH as the precursor 29. In recent years, based on the single Access Article.…”
mentioning
confidence: 78%
“…[18,21,28] Por esta razão, é de se esperar que a modelagem micro-cinética tenha desempenhado um papel mais tímido em eletrocatálise do que em catálise heterogênea. [29][30][31][32][33][34][35][36][37] No presente projeto de pesquisa, foi estudada a modelagem micro-cinética para algumas reações de eletro-oxidação de moléculas de baixa massa molar. [29,38] Mas, nesta tese é apresentado especificamente o desenvolvimento da análise micro-cinética para a reação de eletro-oxidação do ácido fórmico (FAEOR, Formic Acid Electro-Oxidation Reaction) sobre platina policristalina, propondo uma alternativa para determinar os parâmetros do modelo de uma perspectiva top-down, [29,38,39] Functional Theory), [23,59,60] permitem descrever a adsorção, a quebra e a formação de ligações a partir de primeiros princípios, à luz de sistemas catalíticos simplificados.…”
Section: Lista De Abreviaturas E Siglasunclassified
“…O valor de 𝑁 𝑡𝑜𝑡 corresponde à densidade atômica em uma superfície policristalina limpa de platina. Este valor foi determinado pela densidade de carga de 210 𝜇𝐶 𝑐𝑚 −2 para a adsorção/dessorção de uma monocamada35,69,141,142] No entanto, como mencionado nos capítulos anteriores, em sistemas eletrocatalíticos complexos esta situação idealista não é frequente porque, mesmo no caso de um mecanismo bem aceito, os parâmetros cinéticos de todos os passos de reação não são conhecidos ou porque aqueles obtidos por primeiros princípios ou por estudos de espectroscopia não são determinados com a precisão necessária para reproduzir resultados experimentais usando um modelo micro-cinético. Nesse caso, um procedimento fenomenológico iterativo para determinar os parâmetros ausentes é uma alternativa, em que os valores de teste para parâmetros desconhecidos podem ser dos sistemas em estudo.…”
unclassified
See 1 more Smart Citation